Evaluation of promising varieties of winter barley in order to obtain high-quality raw materials for the production of bulky feed - N. I. Devterova (Новые технологии, 2022)
The influence of the use of fertilizer doses at different intensity of tillage on the yield and quality of green feed based on winter barley varieties Romance, Kondrat, Dobrynya, Carioca was studied. The research was carried out in 2018-2020 in the Republic of Adygea on low-humus heavy-duty heavy-clay merged leached chernozems according to the method of field experience of B.A. Dospekhov. It was revealed that disking reduced the productivity of the green mass of various varieties of winter barley by 14,0–41,0%; the average yield for both processing methods varied from 5,75 to 11,2 t/ha. It was found that the most effective method of cultivation was the introduction of 60 kg of d.v. N by background, by both methods of processing, but plowing options are preferable in terms of yield. The use of this method of cultivation allowed to obtain the highest level of yield on these options for all studied varieties: Romance 15,3 t/ha, Dobrynya 14,6 t/ha, Kondrat 14,2 t/ha, Carioca 7,4 t/ha (on average for both methods of processing). The nutrient content in 1 kg of dry matter of feed varied from 8,02 to 11,0% crude protein; 11,1–11,74 MJ of exchange energy; 1,04–1,14 KE. The green mass of the Kondrat, Carioca, Romance varieties is classified as low- and medium-protein feeds, however, in terms of the content of feed units and exchange energy, all varieties are Class I feeds. The studied varieties contain an average of 0,42 to 0,605 EQ of cattle (energy feed units) in 1 kg of natural feed. According to the qualitative indicators in 1 kg of dry matter of feed, as well as the content of EKE in 1 kg of natural feed, the advantage belongs to the Dobrynya variety. The best variety in terms of yield, as well as nutritional and energy value for harvesting from 1 ha is the Romance variety.